2019
DOI: 10.1155/2019/2507242
|View full text |Cite
|
Sign up to set email alerts
|

Lactose Malabsorption and Lactose Intolerance in Children with Inflammatory Bowel Diseases

Abstract: Background Insufficient vitamin D and calcium intake associated with the restricted intake of milk and dairy products can lead to poor health outcomes like malnutrition and abnormal bone mineralization. The aim of the study was to estimate the prevalence of primary and secondary lactose intolerance in children with IBD. Methods The study included 107 patients (mean age 14.07 ± 3.58 years; 46.7% boys) which includes 43 patients with Crohn's disease (CD), 31 with ulcerative colitis (UC), and 33 children with fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…A meta-analysis by Szilagyi et al [ 16 ] has shown an increased risk of lactose intolerance only in CD with small bowel involvement, whereas in UC patients the incidence does not differ from the control. Recently, a study involving children affected by IBD reported that the incidence of lactose intolerance does not differ in respect to the general population [ 19 ]. We found a similar prevalence in lactose intolerance in IBD patients as compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Szilagyi et al [ 16 ] has shown an increased risk of lactose intolerance only in CD with small bowel involvement, whereas in UC patients the incidence does not differ from the control. Recently, a study involving children affected by IBD reported that the incidence of lactose intolerance does not differ in respect to the general population [ 19 ]. We found a similar prevalence in lactose intolerance in IBD patients as compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and their guardians provided informed consent. In this group of patients, another study was performed in which the incidence of lactose intolerance, lactose malabsorption and SNP polymorphisms related to hypolactasia were estimated [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we showed that the incidence of SNP of a promoter region of LCT gene, lactose malabsorption, and intolerance does not differ among children with inflammatory bowel diseases from the population [ 9 ]. Only 1/3 of patients with lactose intolerance developed adaptation and returned to a normal diet in the 3 years of observation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The digestive enzyme lactase is important for the breakdown of lactose into glucose and galactose. Insufficient production of lactase and/or β-galactosidase at the brush border of human intestine leads to undigested lactose, which moves to the gut system causing gastrointestinal symptoms such as bloating, diarrhea and abdominal pain (Jasielska and Grzybowska-Chlebowczyk, 2019). Consumption of non-dairy food products or avoidance of dairy products is the primary solution for lactose intolerance.…”
Section: Introductionmentioning
confidence: 99%